Improving Student Clinicians’ Documentation of Lifestyle Modification - Iris Chen; Donna Jin; Robert Rifkin; Sandhya Chandrasekaran; Andrew Leader; David Thomas; Yasmin Meah (Journal of Student-Run Clinics, 2019)
Background: Lifestyle modification is an important component of clinical encounters, particularly in student-run free clinics that provide care for uninsured patients with a high burden of chronic disease. This study aimed to evaluate the effect of two interventions on the rates of documentation of patient diet, exercise, and health goals at East Harlem Health Outreach Partnership (EHHOP), a student-run free clinic affiliated with the Icahn School of Medicine at Mount Sinai.Methods: A quasi-experimental study was performed at EHHOP over 12 weeks from September to November 2015. Rates of documentation of lifestyle modification and health goals discussions were assessed at baseline and following two periods of intervention. Intervention 1 used electronic medical record (EMR) templates for documenting discussions, and Intervention 2 used focused student teaching to prioritize discussion and documentation of lifestyle modification and health goals. Patient characteristics and documentation rates were compared between each of the three time periods.Results: A total of 161 patient visits were included. There were no significant differences in patient characteristics between Baseline (n=54), Intervention 1 (n=50), and Intervention 2 (n=57) time periods. Rates of documentation increased from 48% (Baseline) to 56% (Intervention 1) to 68% (Intervention 2) for diet, 25% to 42% to 53% for exercise, and 22% to 34% to 39% for health goals. EMR-based Intervention 1 was more effective in improving documentation rates for clinicians caring for patients without diabetes, and student teaching-based Intervention 2 was more effective in improving documentation rates for clinicians caring for patients with diabetes.Conclusions: Systemic efforts that incorporate targeted EMR templates and teaching can help promote documentation rates of lifestyle modification discussions in student clinicians.